Effectiveness of HIV AIDS Prevention Program in Kebumen Regency - Nur Khasanah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
The number of HIV/AIDS cases in Kebumen Regency increases every year. In general, HIV/AIDS has a significant impact on the economic, social, and psychological conditions of people living with HIV, both before and after infection. Therefore, the Kebumen Regency Government, through the HIV/AIDS Commission (KPA), is implementing HIV/AIDS prevention efforts. In carrying out these efforts, the KPA is divided into four areas: Prevention, Care, Support, and Treatment, Impact Mitigation, and a Conducive Environment. The implementation of HIV/AIDS prevention efforts needs to be evaluated to determine its effectiveness. Therefore, this research is crucial. This is a qualitative study using primary and secondary data. Data were obtained from employees of the KPA, the Kebumen Regency Health Office, and the Kebumen Regency Peer Support Group. The results of the analysis conducted show that in the Prevention Sector, of the 47 planned activities, 34 or 72% of the activities have been implemented, 6 activities or 13% have been implemented but not optimally, and 7 activities or 15% have not been implemented. In the Care, Support and Treatment Sector, there are 7 planned activities, while the achievement of activities in this sector is that there are 6 activities or 90% have been implemented and 1 activity or 10% has not been implemented. In the impact mitigation sector, there are 7 activity programs with the achievement of 6 activities or 90% have been implemented and 1 activity or 10% has not been implemented. Furthermore, in the Conducive Environment Sector, there are 3 activities.  and these 3 activities have been implemented. Based on this, it can be said that the majority of activities in each sector have been implemented and their implementation has been effective.